Factors controlling matrix turnover in health and disease. (20th July 2007) - Buttle, D.J.
Abstract : The impact of changes in matrix turnover on disease processes is gradually becoming more widely understood and appreciated. Similarly, the importance of interactions between the cellular and acellular components of any given tissue is finally being realized. An unhealthy cell does not make a healthy matrix; likewise an unhealthy matrix often leads to the demise of the cells within it, or at the very least to major changes in cell phenotype. We can therefore no longer investigate these two components in isolation, because the matrix so often contributes to cellular signalling pathways, and these in turn can lead to changes in matrix turnover. This is a long way from the traditional view of the role of the extracellular matrix, or 'ground substance', in filling the spaces between the cells and providing physical support for them. Just over 100 delegates assembled at Sheffield Hallam University for the Joint BSMB (British Society for Matrix Biology)/Biochemical Society Focused Meeting on Matrix Turnover: Mechanisms and Common Denominators on 2–3 April 2007. The stated aim of the meeting was to aid and encourage interactions between scientists working in various areas of matrix biology, and to this end there were sessions on intervertebral disc, turnover in the CNS (central nervous system), fibroses and tumour–stroma interactions, as well as a session covering general topics. The involvement of both the BSMB and Biochemical Society membership increased the potential for interactions between scientists and hopefully increased the value of the meeting for all the delegates. This issue of Biochemical Society Transactions contains papers written by those who gave oral presentations at the meeting. I think it is fair to conclude from their talks and the papers presented here that the 'common denominators' involved in matrix turnover include cytokine and growth factor signalling pathways that control the rates of matrix synthesis and breakdown, and which, in many disease processes, lead to an uncoupling of synthesis and breakdown and thereby the loss of homoeostasis. Evidently, the make-up of the matrix surrounding cells profoundly affects cell phenotype and behaviour through various signalling pathways. Numerous environmental stimuli may trigger these events, and a host of genes are undoubtedly involved in generating predisposing genotypes. Such factors appear to be common to many diseases involving matrix turnover.